Effects of exercise training on the nigrostriatal glutamatergic pathway and receptor interactions in Parkinson’s disease: a systematic review - Ishaq, Shahid; Shah, Iqbal Ali; Lee, Shin-Da; Wu, Bor-Tsang (Frontiers in Aging Neuroscience, 2025)
BackgroundThe excitatory imbalance of glutamatergic neurons, caused by insufficient input from dopaminergic neurons, contributes the pathogenesis of Parkinson’s disease (PD). Exercise training is one of the non-pharmacological, non-invasive therapeutic approaches.ObjectiveThis systematic review is the first to summarize the effects of exercise training on the regulation of protein and gene expressions within the nigrostriatal glutamatergic pathway and its receptor interactions in animal models of Parkinson’s disease (PD).MethodologyThe PubMed, Web of Science, and Embase electronic databases were searched, and 9 out of 96 studies that met the PRISMA guidelines were included. These studies received a CAMARADES score ranging from 4 to 6 out of 10. The included studies utilized pharmacologically induced PD models in mice or rats with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) or 6-hydroxydopamine (6-OHDA). The majority of studies (89%) employed treadmill training, while 11% used voluntary wheel running, with training protocols consisting of 5 days per week for 4 weeks.ResultsExercise training reduced extracellular glutamate (Glu) and increased the expression of GLT-1, GS, Gln, and mGluR2/3 while down-regulating VGULT1 in the presynaptic terminal of the glutamatergic neurons within the nigrostriatal pathway in PD animal models. It also downregulated mGluR5 and modulated the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits: GluA1 was downregulated, inhibiting long-term potentiation, while GluA2 and GluA3 were upregulated in the nigrostriatal pathway in PD animal models. In addition, the exercise training downregulated the N-methyl-D-aspartate (NMDA) receptors, Arc, Cav1.3, CaMKII, and p-CaMKII in the nigrostriatal pathway in PD animal models.ConclusionExercise training exerted a neuroprotective effect on the glutamatergic pathway in Parkinson’s disease (PD) animal models by limiting excess glutamate in the synaptic cleft. Exercise training modulated the ionotropic receptors and limited the glutamatergic excitatory imbalance within the nigrostriatal pathway in PD animal models. It also improved motor function, including balance, coordination, and gait parameters.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, identifier CRD42024564127